Optimalisasi Peran Fasilitator Pendamping dalam Meningkatkan Kemandirian Usaha Perempuan Prasejahtera - Sayyidina, Nimas Natha Shanna; Suminar, Tri (GUYUB: Journal of Community Engagement, 2025)
Underprivileged women in Indonesia face various challenges in developing their businesses, including limited access to education, technology, markets, and financial services. The mentoring program initiated by Bank Syariah seeks to address these challenges by positioning facilitators as strategic partners. In this context, the primary subjects of empowerment are underprivileged women striving to enhance their entrepreneurial capacity, while facilitators act as agents of change who provide guidance, motivation, and serve as bridges to knowledge and technology. The community service method employed is Participatory Action Research (PAR), with activities conducted in Boyolali Regency, Central Java. This method emphasizes the active involvement of participants from the stages of problem identification, planning, and implementation to evaluation. Mentoring activities were carried out through interviews, participatory observation, entrepreneurship workshops, hands-on practice, and joint reflection sessions. This participatory approach ensures that the real needs of underprivileged women form the foundation for designing materials, methods, and empowerment strategies. The results of the program indicate that the mentoring successfully improved participants’ entrepreneurial skills, particularly in financial management, digital promotion, and business identity development. Indicators of success were also reflected in changes in participants’ attitudes and motivation to manage their businesses independently, increased confidence in marketing products, and greater business visibility through social media. The role of facilitators, who not only delivered materials but also served as motivators, companions, and social change agents, proved to accelerate this transformation. Thus, effective mentoring requires facilitators to master public communication skills, time management, and digital technology to ensure the sustainability of underprivileged women’s business independence.